ChemInform Abstract: Synthesis of ZnSnN2 Crystals via a High‐Pressure Metathesis Reaction. Issue 20 (April 2016) - Kawamura, F.; Yamada, N.; Imai, M.; Taniguchi, T.
Abstract: Crystals of the title compound are prepared from mixtures of ZnF2, SnF4, Li3 N, and LiF (W capsule, 600—1000 °C, 5.5—7.7 GPa).